Inner Life, Politics, and the Secular: Is There a "Spirituality" of Subalterns and Dalits? Notes on Gramsci and Ambedkar. Issue 3 (1st October 2016) - Zene, Cosimo
Abstract : When discussing the plight of subaltern groups, scholars often underline the economic and material troubles suffered by "the poor" through the perpetration of unjust exploitation, unequal distribution of wealth, and more generally, their being subjected to abuse and violence. This narrative frequently includes the means put in place by subalterns to regain a share of power, but the idea of "inner life" or "spirituality" has hardly been considered as part of the process through which subalterns express their agency so as to attain recognition of their "full humanity." A closer analysis of Gramsci's Notebook 11 and other works, however, highlights the relevance of an innovative, transforming, and immanent "spirituality" that necessarily reflects the historical experience of subaltern groups. This is further emphasized by the writings and activity of the Dalit leader B. R. Ambedkar.